4 - Heroes and Villains: Ijaw Nationalist Narratives of the Nigerian Civil War: https://doi.org/10.4314/ad.v34i1.57356 - Nwajiaku-Dahou, Kathryn (Africa Development, 2009)
Numerous explanations of the failure of the Biafran enterprise highlight the absence of legitimacy and support for the Biafran effort among the Niger Delta ‘minorities’. In the aftermath of the Civil War, popular narratives among the Ijaw, arguably Nigeria’s fourth largest ethnic group, tended to tie them closely to the Federal side. In this paper, we examine the transformations of the relationship between Southern minorities and the Biafran cause, with a particular focus on the Ijaw. The fiscal centralization of oil resources that followed the war and the persistence of minority exclusion within the Nigerian polity have encouraged Ijaw elites, and other southern minorities, to review their commitment to Nige- rian federalism. Conflicting tales of the Ijaw nationalist hero Isaac Boro testify to a growing ‘revisionism’ in interpretations of the Biafran War. Today the resur- gence of militant forms of Ijaw ethnic nationalism, against the backdrop of oil community protests which have been taking place since the early 1990s, has given rise to new interpretations of the war, and the creation of new political linkages between Ijaw nationalists, other Niger Delta minorities and Igbo pro- Biafra movements. While resistance to Biafra catalyzed Ijaw nationalism in the fighting and aftermath of the Civil War, Biafra has now become a symbol of contemporary Ijaw nationalism. By drawing on new ‘revisionist’ histories of Biafra, this paper considers the complex interaction of ethnic nationalism, oil and secessionist conflict in Nigeria.